Trade unions’ function in labor dispute resolution as a social partnership entity - Bekbutayeva, Zh.; Sabyr, A.; Tleulov, B. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
This investigation primarily examines the function of trade unions as participants in social partnerships and potential mediators in employment disputes within Kazakhstan. This research aims to elucidate the processes, responsibilities, challenges, and roles of trade unions in workplace relationships. Therefore, this research is useful to both the scientific community and practice, as it contributes ideas for increasing the effectiveness of partnership arrangements. In research uses both the theoretical and practical analysis, a clearly defined logical method, as well as the method of consecutive conclusions to provide a comprehensive analysis of the facet of the trade unions. Some of the findings include the fact that trade unions play a vital role in the process of industrial relations, particularly as a way of addressing conflict and protecting workers’ interests. Key findings highlight the proactive role of modern trade unions in conflict prevention and resolution, as well as challenges they face, such as limited legal authority and political influence. The research identifies collective bargaining and social partnership agreements as important tools for maintaining stable labor relations. It also emphasizes the need for legal and organizational measures to strengthen trade unions’ position in protecting workers’ rights. The research contributes to understanding the evolving role of trade unions in Kazakhstan’s labor relations and offers insights for enhancing their effectiveness in conflict resolution within the social partnership framework.